Occupants in Moisture-Damaged Buildings May be at Risk for Various Symptoms and Inflammatory Reactions: A Case Series Report and Literature Review (Archives of Clinical and Medical Case Reports, 2019)
Objective: Moisture damage in buildings is a common problem. Prolonged exposure to dampness microbiota is a health hazard. There is convincing evidence of increased risk of new asthma or asthma exacerbation due to exposure to dampness microbiota and to decaying products in building materials. In addition, irritation symptoms such as rhinitis, cough, eye problems, eczema, headache, and fatigue have been reported. Certain other diseases might also be associated with exposure to dampness microbiota. Design: Here, we describe four cases of individuals working in water-damaged buildings who in addition to respiratory diseases, suffered from tendinitis, synovitis, arthralgias, muscular pain, cardiac arrhythmias, and urticaria. Conclusion: We review the contemporary literature and present arguments that prolonged or cumulative exposure to dampness microbiota may cause far more complicated disease than asthma alone.